COMPREHENSIVE APPLIED RESEARCH ON INFLECTIONAL AND DERIVATIONAL MORPHEMES IN ENGLISH LANGUAGE ACQUISITION - Savira - Zaniar; Djuwari; Mujad Didien Afandi; Novi Rahmania Aquariza; Nailul Authar (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
Language acquisition, in particular for English as a second language (ESL), involves the knowledge of essential linguistic components such as morphemes. This research, entitled "Comprehensive Applied Research on Inflectional and Derivational Morphemes in English Language Acquisition," examines the acquisition and application of inflectional and derivational morphemes by English Language Learners (ELLs). Inflectional morphemes modify tense, number, or aspect without changing the word class, but derivational morphemes change the meaning and grammatical category of words, therefore facilitating vocabulary development. This study examines morpheme learning patterns, the difficulties learners experience due to the complexity of English morphology and the impacts of their first languages (L1s), as well as the influence of morphemes on overall language ability. The study employs a mixed-methods approach, integrating corpus analysis, experimental activities, and longitudinal tracking of English Language Learners across several educational environments. Interviews and classroom observations provide qualitative insights into cognitive processes and pedagogical practices. The findings indicate that inflectional morphemes are acquired earlier, with learners exhibiting consistent mistake patterns, whereas derivational morphemes provide higher difficulties and are acquired subsequently. Cross-linguistic interference from first languages dramatically impacts learning, and explicit instruction in morphemes greatly enhances learners' proficiency. The research highlights the significance of morpheme awareness in achieving advanced language competency and provides pragmatic ideas for improving the development of morphology-based instructional materials, explicit teaching strategies for ESL/EFL classrooms, and curriculum recommendations that integrate systematic morphological awareness training into English language learning. These findings emphasize the importance of morphology-focused instruction in supporting learners’ linguistic competence and long-term language development.